Transplanting the adolescent cystic fibrosis patient: can we do it?. (April 2013) - Oshrine, Kathleen; McGrath, Debby; Goldfarb, Samuel
Bilateral lung transplantation remains a treatment for end-stage cystic fibrosis (CF) lung disease when there is no further medical or surgical treatment available. The aim of lung transplantation is to improve patient life expectancy. The consensus view that lung transplantation extends life in children has been challenged. However, challengers have faced alternative explanations of their finding and it is largely accepted that lung transplantation in the adolescent patient population is an important treatment modality. The goal of this article is to address these concerns and assist with developing creative approaches to this known challenging subset of patients. The main focus of this article will be to discuss the looming question: what existing evidence or best practice insights could improve bilateral lung transplantation outcomes for adolescent patients with end-stage CF?